Janowa wizja kapłaństwa Chrystusa i Jego uczniów (J 17) - Wróbel, Mirosław Stanisław (Verbum Vitae, 2007)
In the seventeenth chapter of the Gospel according to St. John, also called the prayer of the High Priest, John’s priestly theology is clearly evident. On the one band Jesus is presented as a Priest: He is the Mediator relating the revelation of the Father; called and sent by the Father; fulfills the will of the Father and knows the Father; reveals to people the Glory of God; it is the New Sanctuary opening up to people entrance into eternal life; "perfected" by doing the "works"; "the hour"- the time of Sacrifice inspired by love. On the other band, His disciples remain called to participate in His priesthood. They ought to accomplish this through: remaining in the teaching-revelation brought by Jesus and brotherly love, by faith, by bringing fruit, and the unity of the ecclesiological community. The Spirit - Paraclete makes it possible for them to fully participate in Jesus’ priesthood, allowing them to participate in His mystery, made present in the sacraments. Jesus the Highest Priest is the model o f true service and sacrifice for the first Christian community. Through the view of priestly theology, John the Evangelist strongly brings out the Father-Son relationship and points out the role of the disciples, who thanks to the strength of the Paraclete can undertake in their lives service and sacrifice for Love.